Effect of hot-etching treatment on shear bond strength of zirconia to resin cement. (17th February 2019) - Lv, Pin; Qu, Meng; Jiang, Ting
ABSTRACT: The purpose of this study was to evaluate the effect of hot-etching surface treatment on the shear bond strength between zirconia ceramics and resin cement. Ceramic cylinders were divided randomly into 10 groups ( n  = 10) according to different surface treatments (blank control; airborne particle abrasion; hot-etching for 10 min; hot-etching for 30 min; hot-etching for 60 min) and whether or not performed thermal cycling fatigue test. Flat enamel surfaces, were prepared from human permanent incisors and were bonded to the zirconia discs. All specimens were subjected to shear bond strength test by a universal testing machine. All data were statistically analysed using one-way analysis of variance and multiple comparison least significant difference tests ( α  = 0.05). Hot-etching for 60 min treatment produced higher bond strengths than the other treatment. Surface treatment of zirconia with a hot-etching solution might enhance surface roughness and bond strength between zirconia and resin cement.